2015
DOI: 10.1039/c4cc08752f
|View full text |Cite
|
Sign up to set email alerts
|

Cascade catalysis – strategies and challenges en route to preparative synthetic biology

Abstract: Nature's smartness and efficient assembling cascade type reactions inspired biologists and chemists all around the world. Tremendous effort has been directed towards the understanding and mimicking of such networks. In recent years considerable progress has been made in developing multistep one-pot reactions combining either advantage of chemo-, regio-, and stereoselectivity of biocatalysts or promiscuity and productivity of chemocatalysts. In this context several concepts, inspired by different disciplines (b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
188
0
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 297 publications
(194 citation statements)
references
References 113 publications
(118 reference statements)
0
188
0
6
Order By: Relevance
“…The basic principle of cascade reactions is also frequently used in biocatalysis, using enzymes in isolation, as well as in combination with chemocatalysts (see Fig. 1 and Box 1 for definition of terms) [1][2][3][4][5][6][7] . As there is no need for purification and isolation of intermediates, operating time, production costs and waste are reduced, and concomitantly, overall yields are improved.…”
mentioning
confidence: 99%
“…The basic principle of cascade reactions is also frequently used in biocatalysis, using enzymes in isolation, as well as in combination with chemocatalysts (see Fig. 1 and Box 1 for definition of terms) [1][2][3][4][5][6][7] . As there is no need for purification and isolation of intermediates, operating time, production costs and waste are reduced, and concomitantly, overall yields are improved.…”
mentioning
confidence: 99%
“…Anyhow, cascade biocatalysis becomes particularly sophisticated yet appealing when redox-neutral (see Section 'Cofactor regeneration') or recycling cascades [47] are designed. A couple of excellent and comprehensive reviews on synthetic cascade reactions can be suggested to the reader [48][49][50].…”
Section: Multi-step Biocatalysismentioning
confidence: 99%
“…The attention in the biocatalysis community increased significantly towards cascade reactions in the past decade (Bayer et al 2015;Kohler and Turner 2015;Muschiol et al 2015). Synthesis of highly complex molecules based on multienzyme processes, inspired by Nature's paradigm, become more and more important.…”
Section: Bvmos Applied In Cascade Type Reactionsmentioning
confidence: 99%